A quantitative sampling method for elastic and electromagnetic sources - Liu, Xiaodong; Shi, Qingxiang (Journal of computational physics, 2025)
This study introduces an innovative sampling method for reconstructing elastic and electromagnetic wave sources from far-field patterns. We show that the proposed indicators in the form of integrals with full far field patterns are exactly the source functions. These results simultaneously establish the uniqueness of the inverse source problem and provide a theoretical justification for the sampling scheme. For practical implementation constraints involving sparse sensors and discrete frequencies, we formulate a stability estimation framework for discrete indicators. We have also proposed the indicators with partial far field patterns and proved their validity for providing the derivative information of the unknown sources. Numerical examples are presented to verify the accuracy and stability of the proposed quantitative sampling method.